Junk Gypsy : designing a life at the crossroads of wonder & wander - Sikes, Amie; Sikes, Jolie (Touchstone, 2016)
In their first book, the Junk Gypsies--sisters and stars of the popular Texas-born brand and HGTV show--combine big dreams, stories of roadside treasures found, and down-home design projects inspired by epic makeovers for friends like Miranda Lambert, Billie Joe Armstrong, and Sadie Robertson. Amie and Jolie Sikes, the Thelma and Louise of the design world, are the Junk Gypsies: a family with an addiction to flea markets, wanderlust, and Americana inspired design. In their world, cowgirls are heroes, road trips last forever, and junk is treasured. Beginning with a little bit of faith and a whole lot of heart and soul, the sisters travelled the back roads of America like gypsies, collecting roadside trinkets and tattered treasures while meeting kindred spirits and lively characters along the way. With a mix of hippie, rock n' roll, southern charm, and big dreams, these small-town Texas girls became restless wanderers and owners and operators of their dream business and bohemian brand, Junk Gypsy. Filled with stories from their unique journey as well as DIY projects and bohemian inspired designs, Junk Gypsy is a tribute to all the rowdy gypsies, crafty junkers, free-spirited romantics, and true-blue rebels who have ever dared to dream big,"--Amazon.com.